Co-producing a digital educational programme for registered children's nurses to improve care of children and young people admitted with self-harm. (June 2017) - Latif, Asam; Carter, Timothy; Rychwalska-Brown, Lucy; Wharrad, Heather; Manning, Joseph
Despite the increasing prevalence of hospital admissions for self-harm in children and young people (CYP), there is paucity of registered children's nurse (rCN) training or involvement of children to improve care for this often stigmatized patient group. This article describes a participatory approach towards using co-production with CYP and rCN to develop a digital educational programme to improve nurses' knowledge, attitudes and confidence in caring for CYP with self-harm injuries. A priority-setting workshop with rCNs was used to establish consensus of information needs. This was followed by an e-learning content development workshop undertaken with CYP whom had previously experienced hospital admissions for self-harm injuries. Findings from the nurse priority-setting workshop identified three educational priorities: (1) knowledge of self-harm, (2) effective communication and (3) risk management. The CYP subsequently developed these topic areas to ensure the contents and design of the e-learning resource had fidelity by reflecting the experiences of CYP and needs when cared for in hospital. This article illustrates that involving service users to co-develop educational materials is a feasible and important step in designing educational resources and ensures the content is relevant, appropriate and sensitive to both the recipient of care and those responsible for its delivery.